2019
DOI: 10.1002/hep.30788
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Level of Hepatitis B Core Antibody Predicts Spontaneous Hepatitis B e Antigen (HBeAg) Seroconversion in HBeAg‐Positive Children With a Normal Alanine Aminotransferase Level

Abstract: It is not clear whether baseline hepatitis B core antibody (anti‐HBc) level in hepatitis B e antigen (HBeAg)‐positive children with a normal alanine aminotransferase (ALT) level is predictive of spontaneous HBeAg seroconversion. We investigated the correlation between anti‐HBc level and the natural course of chronic hepatitis B (CHB) virus (HBV) infection in children, particularly the ability of baseline anti‐HBc level to predict spontaneous HBeAg seroconversion during long‐term follow‐up. HBeAg‐positive child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…In a recent study, a higher baseline anti-HBc titer could predict a higher rate of spontaneous HBeAg seroconversion in HBeAg-positive children with a normal alanine aminotransferase (ALT) level. The anti-HBc level could reflect the strength of the anti-HBV immune response in the HBeAg-positive normal ALT phase of CHB (26). A study using liver samples from different phases of CHB was performed to determine the intrahepatic gene signatures.…”
Section: Does B Cell-mediated Humoral Immunity Play a Key Role In Hbvmentioning
confidence: 99%
“…In a recent study, a higher baseline anti-HBc titer could predict a higher rate of spontaneous HBeAg seroconversion in HBeAg-positive children with a normal alanine aminotransferase (ALT) level. The anti-HBc level could reflect the strength of the anti-HBV immune response in the HBeAg-positive normal ALT phase of CHB (26). A study using liver samples from different phases of CHB was performed to determine the intrahepatic gene signatures.…”
Section: Does B Cell-mediated Humoral Immunity Play a Key Role In Hbvmentioning
confidence: 99%
“…Further analysis indicated that qAnti-HBc was an independent risk factor for moderate-to-severe inflammation in CHB patients and exhibited high diagnostic accuracy for hepatic inflammation in patients with normal ALT levels[ 8 ]. A recent study by Chen et al [ 17 ] reported that serum qAnti-HBc levels could reflect the degree of hepatic inflammation in children infected with HBV who have normal ALT levels. Together, these findings suggest that serum qAnti-HBc is a promising biomarker of hepatic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…When HBeAg+ is detected in blood, it indicates that the HBV replicates in large numbers and is highly infectious. 12 Studies have shown that high HBV DNA load is an independent factor of liver fibrosis and an independent predictor of significant liver necrosis inflammation. Furthermore, liver histological stage and grade were higher in patients with high HBV DNA load by stratification.…”
Section: Discussionmentioning
confidence: 99%